Species Diversity of Freshwater Fish in Lake Toba using Shanon Wiener - Rizalatul Qomaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
The diversity of fish in Lake Toba is a natural resource that can increase the fulfillment of the protein needs of the people living around Lake Toba. This research is to find out: (1) the classification of fish found in Lake Toba; (2) the diversity of fish in Lake Toba. Fish found in Lake Toba consist of goldfish (Cyprinus carpio), red devil cichlid fish (Amphilophus labiatus), blue phancax fish (Aplocheilus panchax), Batak fish (Neolissochilus sp), Ikaan Rasbora Tobana (Rasbora tobana), selur fish. Maninjau (Osteochilus vittatus), Mystacoleucus Padangensis Fish (Cyprinidae), Tilapia Mossambica Fish (Tilapia Mosammabica), and Channa Striata Fish (Channa Striata). The diversity index of freshwater fish species in Lake Toba shows a moderate level of diversity, namely H' = 1.831.